Employees' workplace relation civility in workplace: the role of positive relation management and accepted of change - Chua, Bee Seok; Jasmine Adela Mutang; Pan, Lee Ching; Rosnah Ismail (ASR Research India, 2022)
The purpose of the current study was to provide knowledge related to employees' workplace relation civility at work—including, acceptance of change, and positive relation management. We examined the extent to which positive relation management and acceptance of change predict employees' workplace relation civility at work and examined the moderating role of acceptance of change in the relationship between positive relation management and employees' workplace relation civility at work. Respondents were 432 (179 males, 255 females) employees selected randomly using a convenience sampling method from public and private organization sectors in Kota Kinabalu, Sabah, Malaysia. The Workplace Relational Civility Scale was used to evaluate employees' relational civility in the workplace. While the Positive Relation Management Scale was used to measure the positive relation management of employees and the Accepted of Change Scale was used to measure employees’ acceptance of the change. The hypothesized model was tested using structural equation modeling through IBM Statistic SPSS AMOS 23 Program. The fit indices of the modified model (CMIN/DF = 1.561; CFI = .999; GFI = .997; TLI = .991; RMSEA = .036) suggested that the data fit the final model well. The results indicated that from three sub-dimension of positive relation management, only the sub-dimension of caring affect employees' work relational civility positively and significantly. A significant path coefficient was also found from the sub-dimensions of respect and caring to the sub-dimensions of Acceptance to Change: Positive Reaction, Support for Change, Cognitive Flexibility, and Predisposition to change. The results also revealed a significant positive direct effect of the sub-dimension of acceptance to change: Support for change and positive reaction to change, but a negative direct effect of change seeking on employees' work relational civility. The finding indicated only the indirect effect of the sub-dimension of caring on employees' work relational civility through change seeking was significant.